Comparison of peri and post-procedural complications in patients undergoing revascularisation of coronary artery multivessel disease by coronary artery bypass grafting or protected percutaneous coronary intervention with the Impella 2.5 device. Issue 4 (1st June 2019) - Becher, Tobias; Baumann, Stefan; Eder, Frederik; Perschka, Simon; Loßnitzer, Dirk; Fastner, Christian; Behnes, Michael; Doesch, Christina; Borggrefe, Martin; Akin, Ibrahim
Abstract: Background: While coronary artery bypass grafting remains the standard treatment of complex multivessel coronary artery disease, the advent of peripheral ventricular assist devices has enhanced the safety of percutaneous coronary intervention. We therefore evaluated the safety in terms of inhospital outcome comparing protected high-risk percutaneous coronary intervention with the Impella 2.5 device and coronary artery bypass grafting in patients with complex multivessel coronary artery disease. Methods: This retrospective study included patients with complex multivessel coronary artery disease (SYNTAX score >22) undergoing either coronary artery bypass grafting before the implementation of a protected percutaneous coronary intervention programme with a peripheral ventricular assist device or protected percutaneous coronary intervention with the Impella 2.5 device following the start of the programme. The primary endpoint consisted of inhospital major adverse cardiac and cerebrovascular events. The combined secondary endpoint included peri and post-procedural adverse events. Results: A total of 54 patients (mean age 70.1±9.9 years, 92.6% men) were enrolled in the study with a mean SYNTAX score of 34.5±9.8. Twenty-six (48.1%) patients underwent protected percutaneous coronary intervention while 28 (51.9%) patients received coronary artery bypass grafting. The major adverse cardiac and cerebrovascular event rate was numerically higher in the coronary artery bypass grafting group (17.9 vs. 7.7%; P =0.43) but was not statistically significant. The combined secondary endpoint was not different between the groups; however, patients undergoing coronary artery bypass grafting experienced significantly more peri-procedural adverse events (28.6 vs. 3.8%; P <0.05). Conclusion: Patients with complex multivessel coronary artery disease undergoing protected percutaneous coronary intervention with the Impella 2.5 device experience similar intrahospital major adverse cardiac and cerebrovascular event rates when compared to coronary artery bypass grafting. Protected percutaneous coronary intervention represents a safe alternative to coronary artery bypass grafting in terms of inhospital adverse events.